Dari Revolusi ke Reformasi: Analisis Perbandingan Administrasi Publik dan Konstitusi di China dan Rusia - Wulandari, Tri; Abdimas, M. Rafli; Miranda, Diva; Octavia, Avin; Ramadhan, Afif (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Administering public affairs and constitutions in China and Russia differ significantly. China operates under a communist-democratic system dominated by the Communist Party, characterized by a centralized administrative structure. In contrast, Russia transitioned from the Soviet regime to a multiparty political system with a market economy led by a presidential system. A literature review method was employed to analyze relevant sources such as books and journals to understand these differing administrative and constitutional systems. The findings reveal that China vertically integrates its political structure under the dominance of the Communist Party, while Russia exhibits a multi-partypolitical dynamic focused on presidential executive power. This comparison provides insights into how governmental structure and constitution influence political stability and administrative effectiveness in both countries, pertinent to complex international governance and public policy frameworks.